Twelve angry men - Rose, Réginald (Methuen, 2020)
A "guilty" verdict seems a foregone conclusion. But one member of the jury has the will to probe more deeply into the evidence and the courage to confront the ignorance and the prejudice of some of his fellow jurors. The conflict which follows is fierce and passionate, cutting straight to the heart of the issues of civil liberties and social justice.